MATHEMATICAL MODELS SIMULATING THE FORMATION OF THE STRESS-STRAIN STATE OF EPIPLATFORM OROGENS - D. S. Myagkov; Yu. L. Rebetsky (Геодинамика и тектонофизика, 2019)
The sources of the natural stress-strain state (SSS) of epiplatform orogens are investigated by tectonophysical methods based on seismological data. According to the available data, the horizontal axes of the main deviatoric extension are dominant in depressions, while in the ridges of the orogens, the axes of the main deviatorial compression are dominant.Our comparative analysis is focused on SSS of the orogenic crust. It is generally accepted that the sources of such SSS are geodynamic processes, including the pressure on the Eurasian Plate from the Indian Plate, and the small-scale thermogravitational asthenospheric convection. In the mathematical (analytical) simulation technique used in our study, the main criterion for the correctness of models in terms of tectonophysics is the correspondence between the orientation pattern of the principal stress tensor axes in the crust model to the natural data. According to Model I, the lithospheric SSS under lateral compression is less consistent with the sought-for SSS. Model II also gives the results that do not fully correspond to the stress data from tectonophysical reconstructions. However, additional analysis suggests that asthenospheric convection is a more promising (from the point of view of tectonophysics) geodynamic process for explaining epiplatform orogenesis. In our opinion, more complex and probably non-analytical mathematical models should consider this source of loading of the lithosphere as one of the most significant factors in the formation of the orogenic crust SSS in Central Asia.